Change in performance, but not in oxygen cost of running, during cycling-runnig succession - Diaz, V.; Alvarez, M.; Peinado, A. B.; Benito, P. J.; Zapico, A. G.; Calderon, F. J. (Archivos de medicina del deporte, 2008)
Aim: The aim of this study was to evaluate changes in performance and oxygen cost of running (OC) in well trained triathletes after one season. Material and methods: Six professional male triathletes (PRO) and nine elite male young triathletes (YOU), selected by the Spanish Triathlon Federation as the best in their category (under 16), participated in the study. Experimental protocol consisted of two tria s performed in the same moment of two consecutive seasons. In trial 1 subjects completed an incremental test on a cyclergometer to asses the ventilatory threshold1. Trial 2 consisted of 30 min cycling on a cyclergometer at a load corrresponding with the ventilatory threshold determined in trial 1. Inmediately after, subjects run 3000 m as fast as possible on a 400 m track (7,5 laps). All cardiorespiratory variables were measured with a portable metabolic system and OC was calculated each 400m using the formula of di Prampero2. A two way ANOVA (season x lap) with repeated measures was used to evaluate the main effects and changes in speed, OC and cardiorespiratory variables between seasons lap by lap. Signifi cance level was fi xed at p<0.05. Results: An increase in VO2 (9,9% from season 1 to season 2) was observed in YOU group in the second season compared with the fi rst (4227±512 vs. 4649±623 ml•min-1, p<0.05). Also, the speed increased (5,5%) in this group after one season (16.4±0.6 vs. 17.3±0.7 km•h-1). When comparing seasons lap by lap, differences were observed for the speed of running between the 1st and 5th lap in YOU group, but no differences were showed for OC. In PRO group, neither speed nor OC presented differences when comparing seasons lap by lap or the main effects. Discussion and conclusion: Since, OC is the relationship between VO2 and speed, it was surpraising to observe that different changes in these variables did not affect the OC in the YOU group. Moreover, differences were only observed in the first part of the running sector. Then, in agreement with others studies3, 4, we speculate that there is a metabolic rate (in our case expresed as ml O2•min-1•km-1) that is fi xed in a feedfoward manner in order to prevent peripheal fatigue, althought others factors such as mechanical efficiency should be considered. On the other hand, there were no changes in the PRO group. First af all, a low statistical power could be related with the absence of differences. Moreover, these triathletes could be experimenting an "steady-state" in their performance5. In conclusion, metabolic factors per se can not explain the improvement on performance, defi ned here as the speed, during cycling-running succession.